Aktualność myśli pedagogicznej i dzieła Edmunda Bojanowskiego - Opiela, Maria (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
We learn the pedagogical thought of Edmund Bojanowski from his rich heritage, which are his writings and the resulting work, and its development - from the analysis of its implementation in practice by the Little Servant Sisters. Its rich resource and character makes that it demands that his pedagogical theory and practice should be read again, to respond to contemporary challenges in the field of education. Knowing how Bojanowski understands this activity, allows to reflect on how it can be realized today using the achievements of pedagogical sciences and educational practice. On this basis are constructed: indications and programs of pre-school education, care and educational work in various institutions operating in the system of education and social assistance.